Genome-Wide Association Study Reveals Novel Marker-Trait Associations (MTAs) Governing the Localization of Fe and Zn in the Rice Grain - Bollinedi, Haritha; Yadav, Ashutosh Kumar; Vinod, K. K.; Gopala Krishnan, S.; Bhowmick, Prolay Kumar; Nagarajan, M.; Neeraja, C. N.; Ellur, Ranjith Kumar; Singh, Ashok Kumar (Frontiers in Genetics, 2020)
Micronutrient malnutrition particularly of Fe and Zn affects around 3 billion people globally and is especially severe in developing countries. More than 90% of the Asian population is dependent on rice based diet, which is low in these micronutrients resulting in hidden hunger. In the present study, evaluation of a set of 192 Indian rice germplasm accessions grown at two locations for Fe and Zn in brown rice (BR) and milled rice (MR) revealed significant variation in these rice germplasm for these micronutrients. The grain Fe concentration was in the range of 6.2 - 23.1 ppm in BR and 0.8 - 12.3 ppm in MR while grain Zn concentration was found to be in the range of 11.00 - 47.00 ppm and 8.20 - 40.80 ppm in the BR and PR respectively. Grain Fe exhibited maximum loss upon milling with a mean retention of 24.9 % in milled rice while Zn showed a greater mean retention of 74.2% in milled rice. Three sub-populations identified in the association panel depicted distinct trait distributions. Genome wide association study (GWAS) was carried out implementing farmCPU model to control population structure and kinship and resulted in the identification of as many as 29 quantitative trait loci (QTLs) with significant association for these traits viz. FeBR (6 QTLs) FeMR (7 QTLs), ZnBR (11 QTLs), ZnMR (5 QTLs), which could explain phenotypic variance from 2.13 to as high as 53.32%. The QTLs of correlated traits showed co-localization signifying the possibility of their simultaeneous improvement. The robust QTLs identified in the study could be valuable resources for enhancing Fe and Zn concentration in the rice grainand addressing the problem of Fe and Zn malnutrition among the rice consumers.